Número cromossômico e heterocromatina em espécies do gênero Oxalis L. (Oxalidaceae R.Br.). - Alves, William Santana (2020)
Oxalis L. is the largest genus of the Oxalidaceae family, with approximately 500 species, divided into four subgenera: Trifidus, Monoxalis, Oxalis and Thamnoxys. The subgenus Thamnoxys has a wide morphological diversity, accompanied by an unusual karyotype variation, with most diploid species, with n = 5, 6, 7, 8, 9 and 11. The phylogenetic relationships of the group have not yet been fully elucidated. In this work, we analyzed through the CMA/DAPI staining, the karyotype of 13 species and a subspecies of Oxalis from the sections Polymorphae, Thamnoxys and Holophyllum, Hedysarioideae and Phyllodoxys, with the objective of characterizing the karyotype of these taxa, looking for chromosomal marks understand the chromosomal evolution of the group. Root tips were pre-treated with 8Hq for 24 hours and then fixed in Carnoy. The slides were prepared using the 60% acetic acid crushing method and aged at room temperature. Then, the best slides were stained with Chromomycin (CMA) and 4 ', 6-Diamidino-2-Phenylindole (DAPI) and photographed. The predominant chromosome number among the species analyzed was 2n = 10, except in O. puberula with 2n = 20 (sect. Polymorphae) and in O. hedysarifolia species with 2n = 12 and O. frutescens with 2n = 24, both belonging to the section Thamnoxys. In general, the species presented similar karyotype formula with metacentric, submacentric and acrocentric chromosomes. The double staining with fluorochromes revealed only CMA+ bands, in the terminal position of the short arm. The basic number x = 5 is suggested, due to the frequency that is found in the species in this work in the species of the subgenus Thamnoxys. Thus, it is suggested that among angiosperms, the species of the subgenus Thamnoxys is one of the ones that most show karyotype asymmetry. The enrichment of plant cytotaxonomic data of species belonging to the subgenus Thamnoxys, including the determination of the chromosome number and more complete phylogenetic analyzes, is still necessary to elucidate the basic ancestral number of the genus and what are the main mechanisms involved in the chromosome evolution of the group.